A study of factors that influence the Pharmacy Value Added Services (PVAS) adoption in Pharmacy Department of Hospital Sultan Ismail (HSI), Johor Bahru - Abdul Wahid, Abdul Azim Zabidi; Abdul Razak, Ellia Shairra; Rosman, Mohd Rosalaini (2018)
Background: Pharmacy Value Added Services (PVAS) are an innovative dispensing system created to provide an alternative means of collecting partial drug supply to improve the delivery of pharmaceutical care to patients. This includes, Pharmacy Drive Through, Postal Medicine, Integrated Drug Dispensing System and SMS and Collect. However, despite the convenience and advantages of PVAS, patients' adoption rate is still low. Objectives: To explore patients' understanding, beliefs and expectations towards PVAS in Malaysia as well as determining the factors that facilitates and impedes PVAS adoption. Furthermore, the study also aims to assess patients' knowledge and awareness regarding PVAS. Methods: A descriptive and regression survey was conducted from November 2017 till December 2017 at the Ambulatory Pharmacy. The cross-sectional, questionnaire based study was administered to a total of 100 patients with their consent inclusive only to patients not registered to PVAS. The mean score analysis was used to determine the main factor that impedes PVAS adoption. Results: The main factor with the highest mean score (4.8) is information about PVAS not widespread among public people. Conclusion: The lack of awareness towards PVAS impedes adoption by patients. Hence, to increase PVAS adoption among Malaysians, it is strongly suggested to make PVAS well-known to the patients who are collecting repetitive supply from government pharmacies.